(untitled) (Marketing Journal, 2025)
This article examines the theoretical foundations of Agile and green management, exploring their interrelation and integrated application in organizations. Agile promotes rapid adaptation and efficient management, while green management focuses on ecological sustainability and rational resource use. Their integration supports sustainable development across economic, social, and environmental dimensions. The article also highlights international experience and the prospects of implementation in the context of Uzbekistan.